The anticancer activity of ethanol extract of Chromolaena odorata leaves in 7,12-Dimethylbenz[a]anthracene in (DMBA) induced breast cancer Wistar rats (Rattus novergicus) - Yusuf, Hanifah; Kamarlis, Reno Keumalazia; Yusni, Yusni; Fahriani, Marhami (Pharmacia, 2021)
Background: Breast cancer chemotherapy with standard drugs such as doxorubicin will induce cardiotoxicity. Therefore, this study aims to evaluate the anticancer activity of C. odorata leaves extract in DMBA induced breast cancer on rats. Methods: Seven groups of Rattus novergicus were used: Four treatment groups of C. odorata extract (500, 1000, 2000, and 4000 mg/kg BW), normal control, breast cancer control, and doxorubicin treatment group. The number, volume, and weight of the nodule and the rats' body weight were compared among groups. Data was analyzed using paired t-test or one-way ANOVA with post hoc analysis as appropriate. Results: Significant decline of the number, volume, and weight of cancer nodules was observed in the treatment group (p < 0.001). The weight of the cancer nodule at week 16 th was also significantly reduced in G Co2000 compared to G doxo (p < 0.0001). A significant increase in body weight was also dose-dependent, especially at week 11 th (p < 0.05 in all comparisons) and week 16 th (p < 0.001 in all comparisons). Conclusion: This study suggested that the ethanol extract of C. odorata leaves has anticancer and antiproliferative activity.